INTENSI PEMBELIAN HIJAU (GREEN PURCHASING): KERANGKA TEORI SOSIALISASI KONSUMEN DAN PERAN MODERASI KEBUTUHAN AKAN KEUNIKAN KONSUMEN - Rahmat Syarif; Andi Jamiati Paramita (Departemen Manajemen, 2022)
The development of economic and human activities have brought some detrimental effects on environment. This phenomenon then raises the people awareness to take action on preserving environment by buying and consuming green products that have less negative impact on environment. Through the perspective of consumer socialization approach, this current study has explored whether peer communication, green advertising, and eWOM in social media have an influence on consumer’s green purchase intention as well as examined the moderation effect of consumer’s need for uniqueness. By using an online survey with purposive sampling method, 267 responses have been collected and analysed by SEM PLS approach through SmartPLS software. This study founds that while 1) peer communication has a non-significant correlation to green purchase intention, 2) green advertisement and 3) eWOM in social media significantly and positively influence the consumer’s green purchase intention. However, it is also found that need for uniqueness does not have a moderation effect on 4) peer communication, 5) green advertisement, and 6) eWOM in social media. Some managerial implications and recommendations for future research are also elaborated in this research.